INTEGRASI PENYINARAN DENGAN SINAR UV PADA PROSES INVERSI FASE UNTUK PEMBUATAN MEMBRAN NON-FOULING - Addina Nur; Dini Karunia Sari; Heru Susanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Fouling is a serious problem that can reduce the performance of the membrane. Therefore the provision of a membrane with low fouling (non-fouling) is an important thing to do. Non-fouling membrane preparation can be done in two ways, namely modification of the membrane surface after it is created (post-modification) and with mixing (blending) during the manufacturing process. However, the surface modification requires an additional step, while the blending method, produced modification is less stable because there is only mixed without a chemical bond. This paper presents the process  of Ultrafiltration membrane (UF) of polyether sulfone (PES) by mixing polyethylene glycol (PEG) as an additive and exposed to ultraviolet (UV) that will form a non-fouling membranes are stable. In general, the experiment was conducted on the preparation of the solution casting, followed by irradiation with UV light before it immersed in water for one day and dried. The research was carried out by varying the concentration of PEG, photo-initiator benzophenon, type of UV rays, and long irradiation. Characterization of membrane permeability measurements made with pure water, the appearance of the membrane surface with a scanning electron microscope (SEM) and determine the functional groups on the membrane by FTIR. The results showed that irradiation with UV light and the PEG has a significant influence on the characteristics and performance of the membrane.